A Gricean Analysis of Maxim Flouting in Inside Out (2015) and Inside Out 2 (2024) Movie - Prameswari, Galuh Nastiti Citra; Pradipta, Bramantya (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study examines the flouting of Gricean maxims in the animated films Inside Out (2015) and Inside Out 2 (2024). Using Grice’s Cooperative Principle (1975) as the theoretical framework, this research identifies the types of flouting maxims and analyzes how they contribute to character interactions. A descriptive qualitative method was used to analyze 52 utterances from the movies. The findings show that all four types of maxims were flouted: manner (19 instances), relation (15), quality (9), and quantity (8). The data of this study are the utterances from the movies Inside Out (2015) and Inside Out 2 (2024). These floutings were used by characters to express sarcasm, avoid direct responses, or convey emotions indirectly. For example, characters like Anxiety and Riley often flouted the maxims to reflect inner conflict or nervousness, while others used flouting to create humor or shift the topic. The study concludes that flouting maxims in these films serves not only as a pragmatics device but also strengthens emotional expression and character development. This pragmatic strategy enriches the dialogue and makes character interactions more realistic. By understanding these instances of maxim flouting, viewers and learners can develop better interpretive skills and communication awareness.